Tunable High-Performance Microwave Absorption and Shielding by Three Constituent Phases Between rGO and Fe3O4@SiO2 Nanochains - Li, Chao-Qin; Xu, Wei; Ding, Ruo-Cheng; Shen, Xun; Chen, Zhi; Li, Mao-Dong; Wang, Guang-Sheng (Frontiers in Chemistry, 2019)
With the aim of achieving high microwave absorption and electromagnetic shielding performance, reduced graphene oxide (rGO) and Fe3O4@SiO2 nanochains are successfully combined at various mass ratios. By selecting the right mass ratio, an rGO/Fe3O4@SiO2 composite with excellent microwave absorption properties is obtained, and, due to the addition of highly conductive rGO, the desired shielding effectiveness is also achieved. The reflection loss (RL) value of the composite can reach −48.34 dB with a mass ratio of 1:1, and the effective bandwidth (<-10 dB) can cover 4.88 GHz at a thickness of 2.0 mm. Moreover, the composite with a mass ratio of 4:1 exhibits outstanding electromagnetic shielding performance, which also broadens its fields of application. This outstanding microwave absorption and electromagnetic shielding performance indicate that the composite can potentially be employed as a multi-functional material.